INNOVATIONS IN THE ENGLISH EDUCATIONAL LANDSCAPE OF KAMPUNG INGGRIS PARE AS AN ENGLISH VILLAGE-BASED IMMERSION PROGRAM - Pratiwi, Widya Rizky (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
In recent years, immersion programs have become increasingly recognized as a powerful asset in second language education, proving their effectiveness in bolstering students' linguistic skills and proficiency. It is a literature study that integrates various sources, including scholarly articles, books, conference papers, theses, and relevant publications. The review examines the evolution of English Village-based immersion programs, particularly emphasizing Kampung Inggris Pare in Indonesia, and delves into the role of immersion programs in language education. The gathered literature is extensively analyzed, involving thorough reading, data coding, theory integration, and argument summarization from previous researchers. The study revealed that Kampung Inggris Pare, as an English Village-based immersion program, has evolved into a thriving hub for language learning in Indonesia, offering diverse and immersive experiences for participants. The findings are presented to educational practitioners to offer insights into the implementation and effectiveness of English Village-based immersion programs, particularly in Indonesia. This study contributes to the field of TEFL by offering insights into the development and effectiveness of English Village-based immersion programs, with a focus on Kampung Inggris Pare in Indonesia. Keywords: Education, English Village, Immersion Program, Literature Study, TEFL.